1975
DOI: 10.1136/hrt.37.10.1085
|View full text |Cite
|
Sign up to set email alerts
|

Association of secundum atrial septal defect with abnormalities of atrioventricular conduction or left axis deviation. Genetic study of 10 families.

Abstract: A genetic analysis was made of rofamilies in which the propositi had a secundum atrial septal defect associated with abnowrmal atrioventricular conduction (first, second, or third degree heart block) or unexplained left axis deviation or a combination of these conduction disturbances. Diagnostic information was available on 51 (8I%) of the first degree relatives. Three of the families appeared to be examples of a new syndrome which, with variable expression, was inherited as a non-sex-linked autosomal dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Criteria for right atrial enlargement are fulfilled in 35% of patients. 21 In inferior leads, a notch near the apex of the R wave, coined "crochetage," has been correlated with ASD. 23 In 1560 adults and adolescents, 73.1% of patients with ASDs displayed this pattern, with a specificity of 92% when present in all inferior limb leads.…”
Section: Electrocardiography In Achd Ostium Secundum Atrial Septal Dementioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for right atrial enlargement are fulfilled in 35% of patients. 21 In inferior leads, a notch near the apex of the R wave, coined "crochetage," has been correlated with ASD. 23 In 1560 adults and adolescents, 73.1% of patients with ASDs displayed this pattern, with a specificity of 92% when present in all inferior limb leads.…”
Section: Electrocardiography In Achd Ostium Secundum Atrial Septal Dementioning
confidence: 99%
“…PR prolongation is seen in 6% to 19% of patients and uncommonly progresses toward higher-degree AV block, 20 with complete block rarely reported. 21 The QRS axis is usually between 0°and 180°and is often vertical (60°to 90°). Right-axis deviation is common in adults with associated pulmonary vascular disease.…”
Section: Electrocardiography In Achd Ostium Secundum Atrial Septal Dementioning
confidence: 99%
“…Earlier, Emanuel et al had proposed a genetic connection to rationalize left axis deviation and prolonged AV conduction in patients with secundum ASD [5]. Mutations in the transcription factors of NKX2.5 and GATA4 genes are found to be associated with nonsyndromic ASDs.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that all available relatives should also be examined when unexplained left axis deviation or prolonged AV conduction is observed in a patient with a secundum ASD [5]. Earlier, Emanuel et al had proposed a genetic connection to rationalize left axis deviation and prolonged AV conduction in patients with secundum ASD [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation